Different coding characteristics between flight and freezing in dorsal periaqueductal gray of mice during exposure to innate threats - Denghui Liu; Shouhao Li; Liqing Ren; Xinyu Liu; Xiaoyuan Li; Zhenlong Wang (Animal Models and Experimental Medicine, 2022)
Abstract Background Flight and freezing are two vital defensive behaviors that mice display to avoid natural enemies. When they are exposed to innate threats, visual cues are processed and transmitted by the visual system into the emotional nuclei and finally transmitted to the periaqueductal gray (PAG) to induce defensive behaviors. However, how the dorsal PAG (dPAG) encodes the two defensive behaviors is unclear. Methods Multi‐array electrodes were implanted in the dPAG nuclei of C57BL/6 mice. Two kinds of visual stimuli (looming and sweeping) were used to induce defensive behaviors in mice. Neural signals under different defense behaviors were recorded, and the encoding characteristics of the two behaviors were extracted and analyzed from spike firing and frequency oscillations. Finally, synchronization of neural activity during the defense process was analyzed. Results The neural activity between flight and freezing behaviors showed different firing patterns, and the differences in the inter‐spike interval distribution were mainly reflected in the 2–10 ms period. The frequency band activities under both defensive behaviors were concentrated in the theta band; the active frequency of flight was ~8 to 10 Hz, whereas that of freezing behavior was ~6 to 8 Hz. The network connection density under both defense behaviors was significantly higher than the period before and after defensive behavior occurred, indicating that there was a high synchronization of neural activity during the defense process. Conclusions The dPAG nuclei of mice have different coding features between flight and freezing behaviors; during strong looming stimulation, fast neuro‐instinctive decision making is required while encountering weak sweeping stimulation, and computable planning late behavior is predicted in the early stage. The frequency band activities under both defensive behaviors were concentrated in the theta band. There was a high synchronization of neural activity during the defense process, which may be a key factor triggering different defensive behaviors.